2014
DOI: 10.4103/2229-3485.128026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled corticosteroids on systemic inflammation in asthma

Abstract: Background:Recent research using serum high sensitivity C-reactive protein (hs-CRP) has evidenced existence of low grade systemic inflammation in asthmatics whose correlation with various clinical indices is not fully studied.Objective:To investigate the relationship between systemic inflammation and various clinical and treatment characteristics of asthma.Materials and Methods:Forty asthmatics (22 steroid inhaling and 18 steroid naïve) and 40 healthy subjects matched for age and sex were examined cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that treatment of asthma with anti-inflammatory medications such as inhaled corticosteroids results in lower levels of markers of systemic inflammation. 25, 26 The identification of elevated inflammatory markers among participants with persistent asthma in our study is hypothesis-generating; however, we note that their addition to the models did not attenuate the relationship between persistent asthma and CVD events, so we cannot imply a mediated effect. This may be due to partial treatment of inflammation by controller medications.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have demonstrated that treatment of asthma with anti-inflammatory medications such as inhaled corticosteroids results in lower levels of markers of systemic inflammation. 25, 26 The identification of elevated inflammatory markers among participants with persistent asthma in our study is hypothesis-generating; however, we note that their addition to the models did not attenuate the relationship between persistent asthma and CVD events, so we cannot imply a mediated effect. This may be due to partial treatment of inflammation by controller medications.…”
Section: Discussionmentioning
confidence: 65%
“…Various studies conducted for the hsCRP in steroid naïve patients Vs steroid users resuls and its analysis proved that significant increase in hsCRP levels in steroid naïve patients when compared to control groups 17,18 . Our study showed no significant correlation (p=0.093) of hsCRP in patients using inhaled steroids and patients not using ICS , which is in concordance with earlier authers 13,14 .hsCRP and pulmonary function tests documented by earier authors proved that asthmatic patients with high hs CRP have more severe obstruction with low FEV 1 values and also with high hs CRP levels showed significant increase in respiratory symptoms of wheeze, attacks of breathlessness and nocturnal cough it can be concluded hsCRP as sensitive marker for severe asthma 19 .…”
Section: Discussionmentioning
confidence: 98%
“…A dysregulation of protease activity is present in both IBD[ 27 ] and COPD[ 28 ], and is associated with the breakdown of connective tissue components and the ensuing remodeling process[ 1 , 29 ]. Alterations in immune cell homing function[ 1 , 22 ] may explain the low grade chronic systemic inflammation that is present in IBD[ 30 ], COPD[ 31 ], asthma[ 32 - 34 ] and bronchiectasis[ 35 - 38 ]. The hygiene hypothesis, proposing that a lack of exposure to microorganisms during childhood contributes to abnormal immune reactions later in life, may also constitute a common factor linking asthma, IBD and a variety of other conditions[ 39 ].…”
Section: Similarities In Pathogenesis and Risk Factorsmentioning
confidence: 99%